ANALISIS PENGARUH REPUTASI PERUSAHAAN DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN DENGAN KUALITAS PELAYANAN SEBAGAI VARIABEL MODERASI - Rahayu Tiastity, Andi Iswadi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study was to analyze the significance of the effect of the company's reputation, customer trust and service quality on customer loyalty delivery service at PT Pos Indonesia Branch Office Sukoharjo. To analyze whether quality of service moderating influence a company's reputation and customer trust on customer loyalty delivery service at PT Pos Indonesia Branch Office Sukoharjo. In conclusion, no significant influence corporate reputation on customer loyalty delivery service at PT Pos Indonesia Branch Office Sukoharjo, unsubstantiated. There was a significant influence on customer loyalty customer confidence delivery service at PT Pos Indonesia Branch Office Sukoharjo, unsubstantiated. There was a significant effect of service quality on customer loyalty delivery service at PT Pos Indonesia Branch Office Sukoharjo. Quality of service moderating influence of corporate reputation on customer loyalty delivery service at PT Pos Indonesia Branch Office Sukoharjo, not truth. Moderate the effect of service quality on customer loyalty customer confidence delivery service at PT Pos Indonesia Branch Office Sukoharjo, not truth. Keywords: corporate reputation, customer trust, service quality, customer loyalty